Topiramate prevents oxaliplatin-related axonal hyperexcitability and oxaliplatin induced peripheral neurotoxicity. (1st March 2020) - Alberti, Paola; Canta, Annalisa; Chiorazzi, Alessia; Fumagalli, Giulia; Meregalli, Cristina; Monza, Laura; Pozzi, Eleonora; Ballarini, Elisa; Rodriguez-Menendez, Virginia; Oggioni, Norberto; Sancini, Giulio; Marmiroli, Paola; et al.
Abstract: Oxaliplatin (OHP) Induced Peripheral Neurotoxicity (OIPN) is one of the dose-limiting toxicities of the drug and these adverse effects limit cancer therapy with L-OHP, used for colorectal cancer treatment. Acute neurotoxicity consists of symptoms that are the hallmarks of a transient axonal hyperexcitability; chronic neurotoxicity has a clinical picture compatible with a length-dependent sensory neuropathy. Acute OIPN pathogenesis has been linked to sodium voltage-operated channels (Na + VOC) dysfunction and it has been advocated as a possible predisposing factor to chronic neurotoxicity. We tested if topiramate (TPM), a well-known Na + VOC modulator, was able to modify acute as well as chronic OIPN. The project was divided into two parts. In Experiment 1 we tested by means of Nerve Excitability Testing (NET) a cohort of female Wistar rats to assess TPM effects after a single OHP administration (5 mg/kg, iv). In Experiment 2 we assessed TPM effects after chronic OHP treatment (5 mg/kg, 2qw4ws, iv) using NET, nerve conduction studies (NCS), behavioral tests and neuropathology (caudal nerve morphometry and morphology and Intraepidermal Nerve Fiber [IENF] density). In Experiment 1 TPM was able to prevent OHP effects on Na + VOC: OHP treatment induced a highly significant reduction of the sensory nerve's threshold, during the superexcitability period (p-value = 0.008), whereas TPM co-administration prevented this effect. In Experiment 2 we verified that TPM was able to prevent not only acute phenomena, but also to completely prevent chronic OIPN. This latter observation was supported by a multimodal approach: in fact, only OHP group showed altered findings compared to CTRL group at a neurophysiological (proximal caudal nerve sensory nerve action potential [SNAP] amplitude, p-value = 0.001; distal caudal nerve SNAP amplitude, p-value<0.001, distal caudal nerve sensory conduction velocity, p-value = 0.04), behavioral (mechanical threshold, p-value 0.003) and neuropathological levels (caudal nerve fibers density, p-value 0.001; IENF density, p-value <0.001). Our data show that TPM is a promising drug to prevent both acute and chronic OIPN. These findings have a high translational potential, since they were obtained using outcome measures that match clinical practice and TPM is already approved for clinical use being free from detrimental interaction with OHP anticancer properties. Highlights: Oxaliplatin Induced Peripheral Neurotoxicity (OIPN) is a detrimentallate event. No treatment is available. Topiramate (TPM) in animals modulated acute OIPN and prevented chronic OIPN TPM is approved for clinical use and compatible with chemotherapy:its efficacy, given prior to chemotherapy and continued during the treatment, could be tested in a clinical setting.